1979
DOI: 10.1258/002367779781071258
|View full text |Cite
|
Sign up to set email alerts
|

Studies on salmonellosis in the house mouse, Mus musculus

Abstract: Salmonellae were isolated from the faeces from 17 of 170 (10%) wild house mice. Salmonella typhimurium was isolated from 10, S. typhimurium, var. Copenhagen from 2, S. thompson from 1, and S. muenchen from 4. It was concluded that house mice could be a reservoir of infection and play an important role in human and animal salmonellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Serovar Stanley has not previously been reported to be virulent in mice although it has been isolated from rats and is a human pathogen [29]–[34]. Serovars Thompson, Poona, Paratyphi A, and Infantis have never been shown to cause disease in mice, consistent with the results in this study, but they have been isolated from wild mice and rats [35], [36] and from laboratory mice [37]. Consistent with this, we observed that our isolates of Thompson, Poona, and Infantis were recovered from feces two to three weeks after inoculation.…”
Section: Discussionsupporting
confidence: 87%
“…Serovar Stanley has not previously been reported to be virulent in mice although it has been isolated from rats and is a human pathogen [29]–[34]. Serovars Thompson, Poona, Paratyphi A, and Infantis have never been shown to cause disease in mice, consistent with the results in this study, but they have been isolated from wild mice and rats [35], [36] and from laboratory mice [37]. Consistent with this, we observed that our isolates of Thompson, Poona, and Infantis were recovered from feces two to three weeks after inoculation.…”
Section: Discussionsupporting
confidence: 87%
“…76 Differential diagnoses for E. cuniculi infection in mice include infection with Clostridium piliforme (Tyzzer's disease), Corynebacterium kutscheri (pseudotuberculosis), Pseudomonas aeruginosa, salmonellosis, mouse hepatitis virus, ectromelia virus (mousepox), and hematopoietic/lymphoreticular neoplasms. 3,36,46,54,57,62,127 In addition to E. cuniculi infection, experimental E. intestinalis and E. hellem, but not Enterocytozoon bieneusi, infections have been documented in immunocompromised mice. Intestinal and systemic E. intestinalis infections have been documented in several strains of immunosuppressed mice.…”
Section: Infection In Micementioning
confidence: 99%
“…Wild populations harbor food-borne pathogens, especially diseasecausing strains of E. coli, Salmonella, and Listeria (Blackwell, 1981;Fenlon, 1999;Inoue et al, 1992;Ryser and Marth, 1999;Scott, 1959a;Scott and Borom, 1965;Singh et al, 1980;Staff and Grover, 1936;Welch et al, 1941). S. enteritidis is transmitted from infected rats to other rats (Welch et al, 1941) and from infected mice to other mice (Bartram et al, 1940;Shimi et al, 1979). Mice and rats have been implicated in the transmission of Salmonella to poultry (Davies and Wray, 1995;Henzler and Opitz, 1992; National Academy of Sciences, 1969) and to sheep (Hunter et al, 1976).…”
Section: Biological Hazards: Contributing Factorsmentioning
confidence: 99%